PERAN ORANG TUA DALAM PENDIDIKAN ANAK DI JENJANG SEKOLAH DASAR - Irsa Febriyana; Laraswati; Julianingsih; Supriyadi; Amrina Izzatika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education has a very broad meaning, but in general education can be defined as a development process in various aspects, for example knowledge, skills, attitudes and values. Education is not only defined in an academic context but leads to broader aspects of education. Education is not only obtained through formal schools, but families play an active role in providing education to children. Education at the elementary school level is the main foundation for a child's academic and social development because at the elementary school level, it is a crucial stage in character formation and academic development for children. Parents have an active role and great responsibility in introducing education to children. Parents who are actively involved in their children's education are more likely to create a positive learning environment, which has an impact on children's interest and self-confidence. Apart from the important role of parents, good collaboration between parents and teachers can help increase understanding of children's needs and create more appropriate and effective educational strategies. This article aims to explore the role of parents in supporting children's education at the elementary school stage. This research uses a descriptive analytical method and a library research approach, namely a method by examining literary sources in the form of books, magazines and other reading sources. The research results show that parental involvement from academic and emotional aspects contributes significantly to children's learning achievement. Good communication between parents and teachers has been proven to increase the effectiveness of the learning process. Based on the research results, it can be concluded that the impact of parents' active role is very important in creating a positive learning environment.